Perlakuan Akuntansi Aset Tetap Pada Pt Trans Marga Jateng Tahun 2016 - Abiyusa Alizar; Christina Retno Gayatrie (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2018)
Abiyusa Alizar, "Accounting Treatment of Fixed Assets at PT Trans Marga Jateng in 2016", Final Project D3 of Accounting Major at State Polytechnic of Semarang, under guidance of Christina Retno Gayatrie, S.E., M.Si., and Sumanto, S.H., M.H., July 2017, 58 pages.This research aims to determine whether accounting treatment of Fixed Assets at PT Trans Marga Jateng in 2016 has been in accordance with PSAK or not. Data analysis used is comparative method. The research method consisted of data clasification which are qualitative and quantitative, primary and secondary data source. Writing technique used are descriptive and exposition method, and collecting data are interview and literatures study method. The results showed that the accounting treatment of Fixed Assets at PT Trans Marga Jateng in 2016 has been guided by PSAK, but in recognition and measurement of Fixed Assets has not been fully in accordance with PSAK, because there is an error in record the account name and depreciation that will result inaccurate of financial statements.